The Delivery of Special Education Services in Catholic Schools: One Hand Gives, the Other Hand Takes Away - Russo, Charles J.; Massucci, Joseph D.; Osborne, Jr., Allan G. (Catholic Education: A Journal of Inquiry and Practice, 2000)
This article examines legal issues surrounding the delivery of special education to children whose parents have voluntarily enrolled them in Catholic schools. In so doing, the article reviews the Individuals with Disabilities Act (IDEA), its regulations, and case law over the extent to which special education must be provided, the way in which it is delivered, and the quality of services that students in Catholic schools receive. The final portion of the article addresses questions about the delivery of special education in Catholic schools, including guidelines for implementing the new provisions in the IDEA in a manner that avoids running afoul of the Establishment Clause.